Oral transmission and stylistic issues in Malay Asli song in Johor / Fadzril Nidzam Ishak - Fadzril Nidzam , Ishak (2018)
Malay Asli songs is one of the traditional music in Malaysia that taught orally which this music is taught where the learning process involves the students to see, hear, memorize, and imitate from the teacher. In the development of Malay Asli songs, the process of teaching orally has been used because since it is in line with the teaching method and the process of making musical instruments where both are done orally as well. In general, oral traditions are materials that produced by the ancient society (traditional) whether in speech, traditions or practices, among which include folklore, folk songs, dances, games, equipment or objects such as buildings, walls, and others. This study provides a reference of terminologies, singing technique and other issues concerning Malay Asli song to researchers, music activists or individuals. Several topics have been proposed for the teaching and learning process. Learning is easier to understand such as introduction, history of origin, text and pantun, the production of the corresponding tones, exploration of vocal techniques, the appropriate voice, the terms used and the basic steps of studying Malay Asli songs. One of Malaysia’s amazing cultural heritage may be preserved with the existence of this product. Observation of presentation activities is also one of the additional information to researchers. Description of the findings on interviews with several activists or traditional Malay music artists who have had traditional singing experiences for more than ten years as well as being experts of Malay Asli music in schools around Johor who are appointed by the Johor heritage foundation. The conducted interviews were analyzed and they came out to show the agreement of a whole lot of respondents on the excellent development of the product in all aspects. However, setbacks are detected particularly to their v income. That is why propositions on the improvements whereby overcoming the setbacks will be chewed over towards the end.